Nanopatterning by ion beam sputtering in unconventional formats. (14th June 2018) - Kim, J-H; Yoon, S M; Jo, Sujin; Seo, J; Kim, J-S
Abstract: Nanopatterning at solid surfaces by ion beam sputtering (IBS) has been practiced mostly for stationary substrates with an ion beam incident under a fixed sputter geometry. We have released such constraints in the sputter condition. We simultaneously apply two ion beams or sequentially vary the orientation of substrate with respect to an ion beam. We also periodically change either the azimuthal or polar angle of the substrate with respect to an ion beam during IBS. These unconventional ways of IBS can improve the order of the pattern, and produce novel and non trivial nano patterns that well serve as touch stones to refine the theoretical models and thus deepen our understanding of the patterning mechanisms by IBS.